National Trends for Peripheral Artery Disease and End Stage Renal Disease From the National Inpatient Sample Database. (18th June 2021) - De Stefano, Frank; Rios, Luis H. Paz; Fiani, Brian; Fareed, Jawed; Tafur, Alfonso
Peripheral artery disease (PAD), and subsequent chronic limb-threatening ischemia (CLTI), are frequently encountered among patients with end-stage renal disease (ESRD). Their coexistence is less favorable in comparison to patients with ESRD alone. We sought to investigate trends, comorbidities, determinants for cost, and prognostic outcomes in patients with concomitant ESRD and PAD. A retrospective analysis was performed using data from the National Inpatient Sample database from the years 2005-2014. ICD-9 codes were used to identify patients with diagnoses of PAD, CLTI, and ESRD. Pearson's Chi-square, T-test, ANOVA, and multivariate binary logistic regression were used in this analysis. 7, 214, 843 patients with ESRD were identified. Of these, 123, 499 patients were diagnosed with PAD and 102, 447 with CLTI. Compared to ESRD alone, mortality rates increased with PAD and CLTI (5.7% vs. 13.9% vs. 15.9%, P < 0.001). Length of stay in days (7.3 vs. 10.2 vs. 11.1, P < 0.001) and in-hospital costs (59, 872 vs. 85, 866 vs. 89, 016, P < 0.001) were higher with PAD and CLTI, respectively. CLTI demonstrated the highest independent predictor of mortality [OR = 6.93 (6.43-7.46), P < 0.001]. A decreasing trend in the rate of PAD (2005: 1.9% vs. 2014: 1.4%, P < 0.001) and CLTI (2005: 1.6% vs. 2014: 1.1%, P < 0.001) was noted. The presence of coexisting PAD, and furthermore CLTI, in patients with ESRD significantly raised in-hospital mortality, cost, and length of stay. A negative trend in rates of PAD and CLTI were observed. Proactive identification of this high-risk population may lead to accurate diagnosis and tailored therapeutic strategies.